Hearts of sand [large type] : a Gregor Demarkian novel - Haddam, Jane, 1951-2019- (Haddam, Jane, 1951-2019- Gregor Demarkian books., 2014)
Alwych, Connecticut, is the stereotypical old money Connecticut beach town the best families live in mini mansions on Beach Drive, their children go to Alwych Country Day School, and the parents have memberships to the Atlantic Club. And Chapin Waring is the worst thing that ever happened to this town. She was a well turned out debutante from one of the richest families in Alwych until thirty years ago when the young debutante, destined to attend the right school, marry the right man, and have the right life, was revealed to a bank robber and a murderer. She disappeared, never to be heard from again. But Alwych has never forgotten her, or let her friends and family forget. So when after a day of being spotted around town, Chapin turns up dead, stabbed to death in her family's old home, its baffling. To learn why she died and to end the rampant speculation and media coverage Gregor Demarkian, retired profiler for the FBI, is brought in to finally solve the mysteries surrounding Chapin Waring. Not just how and why she died where she did, but where she had been and what happened that night thirty years ago that set everything in motion.